2003
DOI: 10.1161/01.str.0000048845.83285.ac
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Carotid Atherosclerosis Is Associated With Increased Intima-Media Thickness and Elevated Serum Levels of Inflammatory Markers

Abstract: Background and Purpose-Several factors have been held responsible for the development of atherosclerosis. To avoid the masking effect of age, we evaluated correlates of carotid atherosclerosis in patients Ͻ55 years of age. Methods-Plasma lipids, oxidative resistance of low-density lipoprotein, homocysteine, inflammatory markers, plasma viscosity, and red cell deformability were measured in fasting blood samples of 100 subjects: 45 patients with Ͼ30% stenosis of the internal carotid artery, 20 patients with car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 41 publications
10
68
2
2
Order By: Relevance
“…The present findings for WBC count and IMT mirrors those reported previously in participants at risk of diabetes, 15,16 and patients with carotid atherosclerosis 17 and other population studies. 19,20 It appeared to be the increase in lymphocyte number, which was mainly responsible for the overall association with WBCs in the present study, as this was the only predictor to remain significant following full adjustment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present findings for WBC count and IMT mirrors those reported previously in participants at risk of diabetes, 15,16 and patients with carotid atherosclerosis 17 and other population studies. 19,20 It appeared to be the increase in lymphocyte number, which was mainly responsible for the overall association with WBCs in the present study, as this was the only predictor to remain significant following full adjustment.…”
Section: Discussionsupporting
confidence: 91%
“…16 Further, carotid atherosclerosis patients had higher WBC counts than controls and also higher IMT than controls. 17 One large-scale longitudinal study demonstrated that the change in IMT over 9 years was significantly associated with baseline WBC 18 and another showed a positive relationship between WBC and maximal internal carotid plaque thickness, 19 which was particularly strong in Hispanics. In contrast, in a large Japanese study, WBC did not correlate with IMT.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the present results are in line with numerous former crosssectional studies. [37][38][39][40] Despite major advances in treatment of stroke, early identification and prevention of incident events remain crucial, because more than two thirds of all strokes occur without prior symptoms. Recently, Bertges et al 2 demonstrated that progression of carotid artery disease as indicated by duplex ultrasound investigations translates clinically into a substantially increased risk for ipsilateral neurological events.…”
Section: Discussionmentioning
confidence: 99%
“…32 Elevated hs-CRP constitutes an independent predictor of advanced carotid plaques in dyslipidemic subjects, 33 and early-onset carotid atherosclerosis is associated with increased intima-media thickness and elevated serum levels of inflammatory markers. 34 A graded association between hs-CRP and carotid atherosclerosis has been demonstrated in women but not in men. 35 Recently, the American Heart Association has endorsed optional use of hs-CRP to guide physicians in identifying patients without known cardiovascular disease who may be at higher risk than estimated by major risk factors alone.…”
Section: High-sensitivity C-reactive Protein and Other Inflammatory Mmentioning
confidence: 99%